The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/s1677-5538.ibju.2018.0184
|View full text |Cite
|
Sign up to set email alerts
|

Does the experience of the bedside assistant effect the results of robotic surgeons in the learning curve of robot assisted radical prostatectomy?

Abstract: Introduction: The success of the robot assisted radical prostatectomy (RARP) procedures depend on a successful team, however the literature focuses on the performance of a console surgeon. The aim of this study was to evaluate surgical outcomes of the surgeons during the learning curve in relation to the bedside assistant's experience level during RARP. Materials and Methods: We retrospectively reviewed two non - laparoscopic, beginner robotic surgeon's cases, and we di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…The majority of these (21) proved irrelevant, while the full text of one was not in English (Pograjec & Hubert 2019). Two records (Cimen et al 2019a, 2019b) were also excluded for lack of rigour/poor quality as apparently the same dataset was used to achieve different conclusions by excluding one or another variable, and whereas a combined analysis would have seemed more trustworthy. Finally, one other record was excluded (Goldenberg et al 2018) as it proved to be the abstract of an included study (Yu et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of these (21) proved irrelevant, while the full text of one was not in English (Pograjec & Hubert 2019). Two records (Cimen et al 2019a, 2019b) were also excluded for lack of rigour/poor quality as apparently the same dataset was used to achieve different conclusions by excluding one or another variable, and whereas a combined analysis would have seemed more trustworthy. Finally, one other record was excluded (Goldenberg et al 2018) as it proved to be the abstract of an included study (Yu et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Operation time is another important factor in robotic surgery, as we reported in our previous study, it decreases with more experience for both the console surgeon and the bedside assistant ( 21 ). Guzzo et al reported that as the surgeons become more experienced at the bedside, they become more proficient in trocar port placement, docking and undocking, instrumentation and troubleshooting with greater accuracy ( 22 ).…”
Section: Discussionmentioning
confidence: 73%
“…[ 20 23 ] The importance of bedside assistants in terms of surgical outcomes has also been shown in various robotic procedures, including complex gastrointestinal surgery, bariatric surgery, and prostatectomy. [ 13 16 ] However, little attention has been paid to the role of the assistant in robotic thyroid surgery. During BABA robotic thyroidectomy, the bedside assistant has important roles, including aligning the patient and robot in appropriate positions, which enables better control of the console surgeon, changing and mounting devices efficiently, and providing effective suction and irrigation to make a clear surgical field of view.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Previous studies have demonstrated that higher levels of experience of the surgical assistants are associated with reduced operative times, less blood loss, and lower overall complication rates. [ 13 16 ] Moreover, participation of trainees resulted in higher rates of anastomosis leakage, readmissions, re-interventions, and complications. [ 14 ] In contrast, Abu-Ghanem et al [ 17 ] found that assistant's experience levels had no influence on operative outcomes.…”
Section: Introductionmentioning
confidence: 99%